A blind test on floats in extreme waves using a transient potential flow model. Issue 3 (15th September 2020) - Hughes, Jack; Williams, Alison; Masters, Ian
Abstract : Numerical modelling of wave–structure interactions is a cost-effective alternative to physical models in understanding of marine energy device system behaviours and performance, though it is important to establish the reliability of the numerical model first. In this paper, experimental studies in which two surface-piercing floating buoys were subject to a series of focused waves have been modelled using open-source wave energy converter time-domain dynamics modelling software, WEC-Sim. The results were obtained as a blind test, with no knowledge of the experimental data and have not been tuned to match the experiment. Hydrodynamic forces and buoy motions are modelled in the time domain based on the experimental wave elevations, using linear frequency-domain hydrodynamic coefficients estimated by boundary element method solver, Nemoh. Drag coefficients were calculated through computational fluid dynamics, but found to be insignificant. When compared with the experimental results, the WEC-Sim model shows excellent agreement in its prediction of some motions, but less favourable in others. It is thought that non-linear fluid–structure interactions apparent in the experimental data are missed in the WEC-Sim predictions, creating differences in the results. This research study demonstrates that a significant benefit of linear models is their low computational expense when compared to other methods.